Importance of subjective financial knowledge and perceived credit score in payday loan use - Jae Min Lee; Narang Park; Wookjae Heo (International Journal of Financial Studies, 2019)
This study examined the factors associated with consumers' decisions to use payday loans. Using a sample of 24,201 respondents from the 2015 National Financial Capability Study (NFCS), structural equation modeling was used to analyze the relationships among the variables. The results indicated that payday loan use was associated with a series of consumers' socio-psychological factors, including financial knowledge, perceived credit score, credit-card payment problems, and having emergency funds. The findings suggested that, to improve borrowing decisions and industry practices, discussions about consumers' payday loan use and its underlying repayment problems should encompass policy intervention and institutional attention, rather than focusing on behavioral modification at the individual level alone.
Keywords: D12; D14; 330; financial knowledge; National Financial Capability Study; payday loan; structural equation modeling